Superior Magnetic Performance in FePt L10 Nanomaterials. Issue 34 (1st July 2019) - Son, Kwanghyo; Ryu, Gihun; Jeong, Hyeon‐Ho; Fink, Lukas; Merz, Michael; Nagel, Peter; Schuppler, Stefan; Richter, Gunther; Goering, Eberhard; Schütz, Gisela
Abstract: The discovery of the high maximum energy product of 59 MGOe for NdFeB magnets is a breakthrough in the development of permanent magnets with a tremendous impact in many fields of technology. This value is still the world record, for 40 years. This work reports on a reliable and robust route to realize nearly perfectly ordered L10 ‐phase FePt nanoparticles, leading to an unprecedented energy product of 80 MGOe at room temperature. Furthermore, with a 3 nm Au coverage, the magnetic polarization of these nanomagnets can be enhanced by 25% exceeding 1.8 T. This exceptional magnetization and anisotropy is confirmed by using multiple imaging and spectroscopic methods, which reveal highly consistent results. Due to the unprecedented huge energy product, this material can be envisaged as a new advanced basic magnetic component in modern micro and nanosized devices. Abstract : Huge coercivity and high spontaneous polarization with high crystallinity are achieved in FePt nanoparticles. Heat treatment and solving lattice mismatches maintain the L10 ‐phase. Coverage with Au increases superior magnetization. The nanoparticles are realized to be an unprecedented high energy product of 80 MGOe.